Forecasting Range Shifts in Terrestrial Alpine Insects Under Global Warming - Fabio Leonardo Meza‐Joya; Mary Morgan‐Richards; Steven A. Trewick (Ecology and Evolution)
ABSTRACT Anthropogenic planetary heating is disrupting global alpine systems, but our ability to empirically measure and predict responses in alpine species distributions is impaired by a lack of comprehensive data and technical limitations. We conducted a comprehensive, semi‐quantitative review of empirical studies on contemporary range shifts in alpine insects driven by climate heating, drawing attention to methodological issues and potential biotic and abiotic factors influencing variation in responses. We highlight case studies showing how range dynamics may affect standing genetic variation and adaptive potential, and discuss how data integration frameworks can improve forecasts. Although biotic and abiotic factors influence individual species responses, most alpine insects studied so far are shifting to higher elevations. Upslope shifts are often accompanied by range contractions that are expected to diminish species genetic variation and adaptive potential, increasing extinction risk. Endemic species on islands are predicted to be especially vulnerable. Inferences drawn from the responses of alpine insects, also have relevance to species in other montane habitats. Correlative niche modelling is a keystone tool to predict range responses to planetary heating, but its limited ability to consider biological processes underpinning species' responses complicates interpretation. Alpine insects exhibit some potential to respond to rising temperatures via genetic change or phenotypic plasticity. Thus, future efforts should incorporate biological processes by using flexible hybrid niche modelling approaches to enhance the biological realism of predictions. Boosting scientific capability to envisage the future of alpine environments and their associated biota is imperative given that the speed and intensity of heating on high‐mountain ecosystems can surpass our ability to collect the empirical data required to guide effective conservation planning and management decisions.